1988
DOI: 10.1002/jso.2930380104
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival in 242 cases of primary gastric carcinoma

Abstract: Two hundred and forty-two patients who underwent curative surgery for primary gastric cancer between 1965 and 1979 were reviewed, and the influence on survival of the type of surgical treatment, primary tumor location, operative mortality, and stage of disease was analyzed. Operative mortality was significantly increased in patients with multicentric primaries compared to all other sites (P less than .001) and in patients undergoing total gastrectomy versus subtotal gastric resection (P less than 0.001). Stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…A number of reports on the prognosis of patients with malignancies other than EGC have demonstrated that as the number of metastatic lymph nodes increases the posttreatment outcomes worsen [33][34][35][37][38][39][40][41][42]. In this study, however, the number of metastatic lymph nodes was not found to be of prognostic significance.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…A number of reports on the prognosis of patients with malignancies other than EGC have demonstrated that as the number of metastatic lymph nodes increases the posttreatment outcomes worsen [33][34][35][37][38][39][40][41][42]. In this study, however, the number of metastatic lymph nodes was not found to be of prognostic significance.…”
Section: Discussioncontrasting
confidence: 77%
“…Lymph node metastasis has been regarded as a prognostic factor for esophageal [32][33][34][35] and colorectal [36,37] cancer. Many studies focused on gastric cancer have revealed that node involvement is associated with worse outcomes when the analyses include advanced tumors [38][39][40][41][42][43][44]. Even if the depth of tumor invasion is limited to the submucosa, the presence of metastatic lymph nodes is observed to decrease survival rates in esophageal [45,46] and colorectal [47] cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortu nately, the many variables that play an important role in the outcome of noncurative resection have not been well defined and there are no well-established guidelines for surgeons [3,8,11,12], Of 550 patients with primary gastric cancer present ing in an 18-year period, 274 (49.8%) underwent noncu rative surgery. This is comparable with the incidence of advanced gastric cancer reported by many other western authors [1,[3][4][5],…”
Section: Discussionmentioning
confidence: 99%